Analisis Sikap Wirausaha Terhadap Perubahan Status Sosial Ekonomi Dimasa Pandemi Covid-19: Sebuah Tinjauan Pustaka - Kasman Sinring (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
Covid-19 pandemic has become a massive crisis not only in health sector because it has an impact on all sides of life so that it has became the attention of countries in the world today. Covid-19 is a virus that has never been detected before in humans caused by Sars-CoV-2 virus. This pandemic has forced the Indonesian government to implement social restrictions to prevent the increasing number of Covid-19 patients. This has resulted in the disruption of several activities in various fields, especially in the economic sector as well as business actors, both macro and micro. The study carried out in the preparation of the results of this study refers to 8 most recent articles in 2020-2021 which discuss the problems that are currently happening, related to entrepreneurial attitudes towards the decline in socio-economic status using Systematic Literature Review method. The review process of these 8 articles is classified into 2 sub-topic groups. Based on the studies, the results show that entrepreneurial attitudes in responding to the decline in socioeconomic status during the Covid-19 pandemic need to be emphasized by making business adjustments such as adjusting the type of product and market will and also having to be technologically proficient by using various digital platforms such as e-commerce of online application.